2017
DOI: 10.4048/jbc.2017.20.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Basic Facts of Breast Cancer in Korea in 2014: The 10-Year Overall Survival Progress

Abstract: We, the Korean Breast Cancer Society (KBCS), present the facts and the trends of breast cancer in Korea in 2014. Data on the total number of newly diagnosed patients was obtained from the Korea Central Cancer Registry database, other data were collected from the KBCS online registry database, and the overall survival data of patients were updated from Statistics Korea. A total of 21,484 female patients were newly diagnosed with breast cancer in 2014. The crude incidence rate and the age-standardized incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 22 publications
2
95
1
1
Order By: Relevance
“…Similarly, Bae et al showed 15.8% of their cohort presented palpable symptom or nipple discharge which could be detected as a mass. In the present study, however, ultrasound findings were not significant predictors of NAC involvement in comparison with other imaging modalities, probably due to the greater number of sonographically undetected lesions (14 for ultrasound vs 6‐7 for mammograms or MRI) and the large proportion of asymptomatic patients (75.0%) in our study population or relatively younger age at diagnosis in Korean patients than in the Western …”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Similarly, Bae et al showed 15.8% of their cohort presented palpable symptom or nipple discharge which could be detected as a mass. In the present study, however, ultrasound findings were not significant predictors of NAC involvement in comparison with other imaging modalities, probably due to the greater number of sonographically undetected lesions (14 for ultrasound vs 6‐7 for mammograms or MRI) and the large proportion of asymptomatic patients (75.0%) in our study population or relatively younger age at diagnosis in Korean patients than in the Western …”
Section: Discussioncontrasting
confidence: 75%
“…The number of NSM being performed in the United States has increased in recent years . The Korean Breast Cancer Society reported a change from a decrease in the number of mastectomies to a recent steady‐state of mastectomies, and a large increase in the number of breast reconstructions . Although future observations are necessary to confirm whether this trend will continue in Korea, the number of NSM with immediate reconstruction is likely to increase, because the Korean National Health Insurance started covering some of the costs for breast reconstruction since April 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, according to 2014 national cancer statistics for Korea, in a span of 16 years, the incidence of breast cancer steadily increased: 21,402 new cases of breast cancer in women were reported, which was roughly 3.6 times more than the 6,025 cases reported in 1999 (Jung et al, ; Park et al, ). Furthermore, for all stages, the 5‐year and 10‐year overall survival rates for breast cancer were 91.2% and 84.9%, respectively (Park et al, ). Considering the increasing trend of breast cancer incidence and survival rate, it is essential to pay attention to the cancer‐related symptoms commonly experienced by BCS such as CRF, pain, depression, anxiety, sleep disturbance, cognitive impairment and physical limitations (Harrington, Hansen, Moskowitz, Todd, & Feuerstein, ).…”
Section: Introductionmentioning
confidence: 98%